Medical students’ use of caffeine for ‘academic purposes’ and their knowledge of its benefits, side-effects and withdrawal symptoms - Kuan-Hua Lee; Gercois P. Human; Jurie J. Fourie; Willem A.N. Louw; Carol O. Larson; Gina Joubert (South African Family Practice)
Background: Caffeine is often used for its benefits, which include increased vigilance. It does have side-effects, however, such as palpitations and withdrawal symptoms that include headaches and drowsiness. Tertiary education often requires students to study for extended hours, especially during periods of increased workload prior to tests and examinations. Medical students, who have to master a very large volume of academic work in a limited period of time, are no exception. This cross-sectional study investigated caffeine use for ‘academic purposes’ by first- to third-year medical students at the University of the Free State in 2006, and their knowledge of its benefits, side-effects and withdrawal symptoms.